The role of digital media in educating Bangkok’s youth on sustainable consumption and production - Kanchanawongpaisan, Sipnarong; Chayanont, Sunthan; Srison, Wijittra (Kasetsart Journal of Social Sciences, 2026)
This study explores the impact of digital media on sustainable behaviors among 504 university students using Structural Equation Modeling (SEM). Data were collected through stratified random sampling, ensuring a representative cross section of students from various faculties. The survey, administered online via Google Forms from May to October 2023, included comprehensive questions on digital media usage, sustainability awareness, and behavioral intentions. The SEM analysis was performed using AMOS software, with parameters set to identify digital media’s direct and indirect effects on sustainable practices. Findings indicate that while digital media significantly enhances awareness and fosters favorable attitudes toward sustainability, there is a significant gap between these attitudes and actual behaviors. This highlights the urgent need for educational institutions to enhance curricular and extracurricular strategies that effectively translate increased awareness into real-world sustainability actions, aligning with global Sustainable Development Goals. The study’s findings have practical implications for educational institutions, policymakers, and researchers, as they underscore the potential of digital media as an essential educational tool in promoting and achieving sustainability within academic settings.